Sharenting and its association with impulsivity in adults from Argentina and other Latin American nations - Resett, Santiago (2025)
Sharenting or exposure to minors on social networks by adults, such as family members, is a very current problem with social, psychological and legal implications due to the risk that said contents will be used by third parties for malicious purposes. The present study is one of the few existing in Latin American nations. The purpose of this research was to explore the levels of sharenting, determine if gender, age and nationality introduced differences in the scores of this behavior and if impulsivity was associated with sharenting. For this purpose, an intentional sample of 903 adults from Latin America was constituted. They answered the Sharenting Evaluation Scale by Romero-Rodriguez et al. 2022 and the Impulsive Behavior Scale (UPPS-P) by Lynam et al. 2006. The results indicated that women carried out higher levels of sharenting and, at a younger age, higher scores for this behavior. Adults from Argentina showed a higher level of this behavior, compared to those from other nations in the region. Greater the impulsiveness, higher levels of sharenting. The results of this study indicate that demographic, cultural and psychological factors must be taken into account when preventing this problem.